Phytochemical composition and the cholinesterase and xanthine oxidase inhibitory properties of seed extracts from the Washingtonia filifera palm fruit. Issue 37 (8th July 2019) - Floris, Sonia; Fais, Antonella; Rosa, Antonella; Piras, Alessandra; Marzouki, Hanen; Medda, Rosaria; González-Paramás, Ana M.; Kumar, Amit; Santos-Buelga, Celestino; Era, Benedetta
Abstract : The chemical composition and biological properties of palm Washingtonia filifera (Lindl.) H. Wendl. seeds are seldom studied. Abstract : The chemical composition and biological properties of palm Washingtonia filifera (Lindl.) H. Wendl. seeds are seldom studied. Bearing this in mind, the seeds of W. filifera fruits were analysed for their fatty acid and phenolic composition and their antioxidant activity in addition to their cholinesterase and xanthine oxidase inhibitory activities. Seed extracts were revealed as a good source of phenolics with significant antioxidant activity. The phenolic profile mainly consisted of proanthocyanidins or procyanidin dimers B1–B4 among the major compounds. The highest butyrylcholinesterase inhibitory activity was found in the ethanolic extracts of seeds, with IC50 values of 13.73 ± 1.31 μg mL −1 . Seed alcoholic extracts also displayed interesting xanthine oxidase inhibitory activity, with IC50 values ranging between 75.2 ± 17.0 μg mL −1 and 95.8 ± 5.9 μg mL −1 . Procyanidin B1, a major component in the extracts, could be an important contributor to that activity, as it was found to possess good xanthine oxidase inhibition capacity (IC50 value of 53.51 ± 6.03 μg mL −1 ). Docking studies were also performed to predict the binding sites of procyanidins B1 and B2 within the xanthine oxidase structure. In all, W. filifera seeds appear as a promising natural source for the extraction of bioactive compounds with antioxidant and butyrylcholinesterase as well as xanthine oxidase inhibitory potential.